Voices of the invisible presence : diplomatic interpreters in post-World War II Japan - Torikai, Kumiko, 1946- (Benjamins translation library ;, 2009)
Voices of the Invisible Presence: Diplomatic interpreters in post-World War II Japan examines the role and the making of interpreters, in the social, political and economic context of postwar Japan, using oral history as a method. The primary questions addressed are what kind of people became interpreters in post-WWII Japan, how they perceived their role as interpreters, and what kind of role they actually played in foreign relations. In search of answers to these questions, the living memories of five prominent interpreters were collected, in the form of life-story interviews, which were then.